Good Practices for the Management of Fragile Territories Resilience - Pignatelli, Federica; De Vita, Mariangela; Properzi, Pierluigi (TeMA - Journal of Land Use, Mobility and Environment, 2019)
Italy is a territory frequently affected by natural disasters that have a huge impact on urban transformations. The physical and socio-economical reconstruction process of a territory damaged by a traumatic event at first pursues the path of emergency management and subsequently the rehabilitation of the damaged areas. These political and economic strategies are still unsystematic, so it is difficult to foresee eithers long or short term effects. This paper presents an analysis carried out on the city of L'Aquila following the earthquake of 2009, in which indicators were defined to assess and monitor the reconstruction process. The method used to define the indicators is 'absolute', in such a way as to represent a replicable model that can be adapted to different territorial and emergency contexts. Furthermore, the set of indicators proposed can be used not only to monitor the reconstruction process, but also to guide public policies and to suggest shared strategic guidelines, not originated by the urgency of after-shock conditions. The proposed model is a tool to be used from the early stages of reconstruction, in order to predict the outcome of the reconstruction itself. In this way, it is possible to manage urban transformation in a coherent and organic way in all its phases by adopting a single tool. The use of the model shown in the research also makes it possible to enhance the resilience of a territory by exploiting its intrinsic characteristics.